(untitled) (Bangladesh Journal of Plant Taxonomy, 2005)
The paper deals with four taxa of the family Araceae as new records for Bangladesh, namely, Aglaonema commutatum Schott, A. marantifolium Blume, Colocasia mannii Hook. f. and Remusatia vivipara (Roxb.) Schott. An up-dated nomenclature, important synonyms, illustrated description, flowering and fruiting times, specimen citation, ecology and geographical distribution for each species have also been given. Key words Four new records, Araceae, Bangladesh DOI: 10.3329/bjpt.v12i2.601 Bangladesh J. Plant Taxon. 12(2): 39-48, 2005 (December)